THE ROLE OF MUBALIGH AND PARENTS IN GROWING CHILDREN'S CHARACTER IN KAMPONG GAYAU SARAWAK MALAYSIA - Edhy Rustan; Miftahul Jannah Akmal (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
This study aims to obtain an overview of how to foster children's character through the role of Islamic education from Mubaligh and contributions of parents in Gayau Pantu Sri Aman village, Sarawak, Malaysia. This study uses a qualitative method with a case study design. The subjects of this study were children aged 10-12 years old. The minority converts are tenheads of families, and the preacher consists of two people who come from the community. Data were collected through interviews and observations. Data analysis refers to the Milles and Huberman model, namely: 1) data collection, 2) data reduction, 3) data presentation, and 4) makingconclusions. The data validity technique used triangulation of data and sources. The results showed that mubaligh and parents play a role in developing children's character by applying social-oriented religious learning. Religion and tolerance are the most dominant characters that grow in children.Â